Finding Francis : One Family's Journey from Slavery to Freedom - West, Elizabeth J., 1957- (Book collections on Project MUSE., 2022)
"Finding Francis, finding family, freeing history. Francis is found. Beyond Francis, a family is found-in archival material that barely deigned to notice their existence. This is the story of Francis Sistrunk and her children, from enslavement into forced migration across South Carolina, Georgia, Alabama, and Mississippi. It spans decades before the Civil War and continues into post-emancipation America. A family story full of twists and turns, Finding Francis reclaims and honors those women who played an essential role in the historical survival and triumph of Black people during and after American slavery. Elizabeth West has created a remarkable 'biohistoriography' of everyday Black resistance, grounded in a determination to maintain enduring connections of family, kinship, and community despite the inhumanity and rapacity of slavery. There is inevitable heartbreak in these histories, but there is also an empowering strength and inspiration-the truth of these lives will indeed set us all free"--